Collected Poems - Ceravolo, Joseph, 1934- (Book collections on Project MUSE., 2012)
A collection of poems penned by a singular American poet. This collection offers a full portrait of the poet's aesthetic trajectory, bringing to light an original voice that was operating at an increasing remove from the currents of the time. From a poetics associated with Frank O'Hara and John Ashbery to an ever more contemplative, visionary poetics similar in sensibility to Zen and Dante, William Blake and St. John of the Cross, this collection shows how the writer's poetry takes on a direct, quiet lyricism.